Albert Einstein A Life Story - Joseph, Mary (Sterling Group, 2012)
Introduce even the youngest readers to historical figures in this easy-to-read series. Simple text highlights the major events in the lives of famous men and women, from their childhood through their adult life. A time line feature at the bottom of each spread captures the important details one at a time, culminating in a complete summary of the person's life on the final page. First Biographies are rich resources for the primary grades. This series explores and supports the standard The History of the United States: Democratic Principles and Values and the Peoples from Many Cultures Who Contributed to Its Cultural, Economic, and Political Heritage, as required by the National Standards for History.
Keywords: Biography